Orthodontic Management of Ectopically Erupted Maxillary Central Incisor: A Case Report - Chaudhary, Nabin Kumar; Giri, Jamal; Gyawali, Rajesh; Pokharel, Prabhat Ranjan (Nepal Journal of Health Sciences, 2022)
Maxillary anterior teeth are often referred to as “social six”; if ectopically placed affect the quality of life of the patient. This article presents a case report of a skeletal class II patient with Angle’s class II malocclusion and ectopically erupted right maxillary central incisor which is managed with fixed orthodontics. This highlights the importance of proper history taking, careful examination, and proper investigations in reaching the diagnosis and formulation of the treatment plan. This case report also explains how the piggyback technique can be used for the traction of ectopically placed maxillary incisors and bring about satisfactory results and improve the confidence and self-esteem of the patient.